Letter - Gillies, William
029-0059-001 Telegraphic Address: "LABREPCOM, SOWEST, LONDON." Telephone: VICTORIA 8016, 8017, 8018, 8019 THE LABOUR PARTY TRANSPORT HOUSE (South Block), SMITH SQUARE, LONDON, S.W.1 Hon. Treasurer.: RT. HON. ARTHUR HENDERSON, M.P. Secretary: J. S. MIDDLETON National Agent: GEORGE R. SHEPHERD December 31, 1937 Mr. V. Tewson, My dear Tewson, I enclose copy of a letter and telegram which which I have sent both to Adler and Schevenels. Yours sincerely, WILLIAM GILLIES Secretary, International Department. Encls. Read the "DAILY HERALD" every day and "LABOUR" and "THE LABOUR WOMAN" every month 292/946/29/59